Antimicrobial Efficacy of Triphala as Root Canal Irrigating Solution in Infected Primary Teeth: An Ex Vivo Study (Indian Journal of Public Health Research & Development, 2020)
Background and Objectives: Dental caries is a common problem encountered in children. Deciduous teeth with deep dental caries can be treated with pulp therapies to allow normal exfoliation process. The process of pulpectomy involves access cavity preparation, cleaning and shaping of the root canal and obturation. Even though all these procedures are essential, irrigation of the root canal during cleaning and shaping is vital in ensuring complete microbial decontamination, which guarantees the success of pulpectomy. Although NaOCl is considered as gold standard among root canal irrigants, the quest for a better irrigant with superior antimicrobial efficacy and biocompatibility was under consideration.Hence, the present ex vivo study was done to evaluate and compare the antimicrobial efficacy of 0.5% Sodium hypochlorite (Dakin’s solution) with 10% Triphala, a herbal root canal irrigant.Results: The study showed a statistically significant difference in the anti-microbial efficacy of 10% Triphala and 0.5% Sodium hypochlorite (Dakin’s solution).Conclusion: The antimicrobial efficacy of 10% Triphala was better than that of 0.5% Sodium hypochlorite (Dakin’s solution) when used as root canal irrigants in infected primary teeth.
Keywords: Triphala, Sodium hypochlorite, Root canal irrigant, Antimicrobial efficacy